Mechanochemical coupling of MGF mediates periodontal regeneration - Ying Zhao; Songbai Zhang; Bo Cheng; Fan Feng; Yue Zhu; Yanli Liu; Junjun Wang; Dehui Zou; Heng Ma; Feng Xu; Min Zhang (Wiley, 2024)
Abstract Clinical evidence shows that the mechanical stimulation obtained from occlusion could enhance periodontal ligament (PDL) remodeling. Mechano‐growth factor (MGF) is a growth factor produced specifically following mechanical stimulus Here, we aim to investigate the mechanical enhancement potential and mechanism of the MGF in PDL regeneration. In vivo study found that MGF produced from the PDL under occlusion force could strongly enhance PDL remodeling. In vitro experiments and mathematical modeling further confirmed the mechanical enhancement effect of MGF for PDLSC differentiation toward fibroblasts. A mechanochemical coupling effect of MGF mediated the enhancement of mechanical effect, which was modulated by Fyn‐FAK kinases signaling and subsequent MAPK pathway. Finally, enhanced PDL regeneration under the mechanochemical coupling of MGF and occlusal force was verified in vivo. There exists an additive mechanical effect of MGF mediated by Fyn‐FAK crosstalk and subsequent ERK1/2 and p38 phosphorylation, which could be developed as an MGF‐centered adjuvant treatment to optimize PDL remodeling, especially for patients with weakened bite force or destroyed periodontium.